Acquisition of sexual orientation and gender identity data among NCI Community Oncology Research Program practice groups. Issue 8 (18th December 2018) - Cathcart‐Rake, Elizabeth J.; Zemla, Tyler; Jatoi, Aminah; Weaver, Kathryn E.; Neuman, Heather; Kazak, Anne E.; Carlos, Ruth; Gansauer, Lucy; Unger, Joseph M.; Pajewski, Nicholas M.; Kamen, Charles
Abstract : Background: Sexual and gender minority individuals face numerous cancer‐related inequities, many of which appear to be underreported. However, to the best of the authors' knowledge, no one has assessed rates of acquisition of sexual orientation and gender identity (SOGI) data within community oncology settings. Methods: Community oncology practices that were part of the NCI Community Oncology Research Program (NCORP) network were asked whether they routinely collected SOGI information and coded this information in their electronic medical records. The proportion of practice groups reporting routine collection of sexual and/or gender minority information was calculated. Potential associations between the collection of SOGI information and practice group–level and state‐level characteristics (from Gallup poll data) were also provided. Results: Twenty‐four percent of the responding NCORP practice groups reported routine collection of sexual orientation information, and 10% reported collection of gender identity information. Practices located in western regions of the United States, practices in states with higher proportions of sexual and gender minority–identifying individuals, and practices with lower proportions of non‐Hispanic patients were more likely to ask patients about sexual orientation and/or gender identity. Conclusions: US oncology practices that participate in research do not frequently collect SOGI information from patients with cancer. Educational initiatives should inform oncology staff and providers about the importance of collecting gender identity and sexual orientation information to improve existent disparities faced by sexual and gender minority patients. Abstract : Only 1 in 5 oncology practice groups routinely collects information on patient gender identity or sexual orientation. The education of health care providers and research personnel is needed to improve the cancer care of this understudied minority population.